The infrared radiation effect to the trismus recovery after odontectomy - Marwan, Arian Reza; Syamsudin, Endang; Karasutisna, Tis (Padjadjaran Journal of Dentistry, 2007)
Impacted was defined as unerupted teeth, it could some pathological conditions such as pain, swelling, trismus, and should be removed by an operative procedure called odontectomy. Nevertheless, this procedure could cause some complications such as pain, trismus and swelling. Trismus was a jaw restricted movement condition caused by inflammation, swelling and pain. Trismus could be cured by analgetic anti-inflammation medicines, and physiotherapy such as jaw movement exercise, massaging, hot wet application and therapy used infrared light. Infrared light was an electromagnetic radiation with a wavelength between 0.7 Î¼m-1000 Î¼m. It could reduce the inflammation in cell structure, pain and less of side effects. The research was carried out to know the infrared effect to the velocity of trismus recovery. Type of research had been used is quacy experimental in a prospective way, using 15 patients with infrared radiation and 15 patients without infrared radiation. The result of research used t-test with Î± = 0.05 indicated that there was significant differences velocity of trismus after odontectomy recovery between infrared radiation and without infrared radiation. This study concluded that the velocity of trismus recovery was faster when applied by infrared radiation.